INTEGRASI NILAI-NILAI KARAKTER BANGSA PADA KEGIATAN PEMBELAJARAN - Anik Ghufron (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: The Integration of the Nations Character Values into IntructionalActivities. One of the crucial problems in the national education system is themoral problem. There is evidence that indicates a moral crisis among students. Thisshows that educational institutions fail to prepare graduates with good morality.To solve this problem, the nations character values need to be integrated in theimplementation of the formal curriculum. By doing so, teachers can help studentsto actualize each learning domain through the competency formulation and thestudents can simultaneously carry out relevant moral actions. Integrating thenations character values into the curriculum can be done in three stages:introduction, implementation, and evaluation. Each stage can improve studentsgood characters based on the formulation of the competency standard. Such anintegration has implications for schools, teachers, parents, and students.Keywords: integration, nations character values, instructional activities